Prism-patterned Nafion membrane for enhanced water transport in polymer electrolyte membrane fuel cell - Kim, Sang Moon; Kang, Yun Sik; Ahn, Chiyeong; Jang, Segeun; Kim, Minhyoung; Sung, Yung-Eun; Yoo, Sung Jong; Choi, Mansoo (ELSEVIER, 2016)
Here, we report a simple and effective strategy to enhance the performance of the polymer electrolyte membrane fuel cell by imprinting prism-patterned arrays onto the Nafion membrane, which provides three combined effects directly related to the device performance. First, a locally thinned membrane via imprinted micro prism-structures lead to reduced membrane resistance, which is confirmed by electrochemical impedance spectroscopy. Second, increments of the geometrical surface area of the prism patterned Nafion membrane compared to a flat membrane result in the increase in the electrochemical active surface area. Third, the vertically asymmetric geometry of prism structures in the cathode catalyst layer lead to enhanced water transport, which is confirmed by oxygen gain calculation. To explain the enhanced water transport, we propose a simple theoretical model on removal of water droplets existing in the asymmetric catalyst layer. These three combined effects achieved via incorporating prism patterned arrays into the Nafion membrane effectively enhance the performance of the polymer electrolyte membrane fuel cell. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: CATHODE CATALYST LAYER; PORE-FORMER; OPTIMIZATION; PERFORMANCE; CARBON; PEMFC; DMFC; CO